POLA DISTRIBUSI KAYU PENGHARA UNTUK INDUSTRI PENGGERGAJIAN DI DAERAH JAWA TENGAH - Rachman Efendi; Subandi Antaatmaja (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Transportation cost in logs distribution by Forest District Administration (KPH) for sawmilling industry are an important component influencing on the structure of whole production cost. In determining the distribution pattern. of logs as raw material for sawmills of Perum. Perhutani, in particular Perum Perhutani unit One, Central Java, more attention should be paid on the efficiency aspect. The aim of this investigation is to determine the optimal allocation of logs for sawmills so as to minimize the total transportation cost. The technique used is linear programming. The result of the investigation is :The Average raw material demand of Cepu sawmill is 3407 cu.m. per year. It rs supplied by 3 forest district administrations (KPH), while Brumbung sawmill (16973 cu.m. per year) is supplied by 8 forest district administrations.The total cost of transporting the raw material is Rp 177.997.530,- or 91,11% of transporting cost of current distribution scheme.